APPLICATION OF CLUSTERING POTENTIAL CREDIT RECIPIENTS USING THE K-MODE METHOD - Yosep Agus Pranoto; Kartiko Ardi Widodo (International Journal of Computer Science and Information Technology, 2024)
This application for clustering potential credit recipients was created as a solution to the problems that arise in the process of applying for a loan in a cooperative. The difficulty arises in determining which applicants are entitled to a loan because of the multiple criteria that are taken into account and the large number of applicants. As a result, the decision-making process takes a long time and is prone to errors. In addition, the decisions made are often subjective. In the development of information technology, a solution can be made by creating a computer-based application using the K-mode method for decision making. This application can be used by related parties to make decisions on the selection of credit acceptance. Based on the tests conducted, the accuracy rate of the application is 95%.